The Role of Architectural Preservation Processes on the Permanence of Heritage Buildings of Value - Qadir, Sham Mustafa; Muhealdeen, Banaz N.; Khayat, Mahmood Ahmed; Maruf, Sherko Karim Kader; Agha, Shava Shirwan Ibrahim (Kurdistan Journal of Applied Research, 2022)
Architectural heritage is all the cultural and civilizational achievements that man inherited from his ancestors, acquiring a qualitative value that has proven its importance and originality in resisting the forces of change, becoming a visual reference. The architectural heritage has been exposed to natural and human factors that caused much damage. This requests to deal with these factors at every level through joint action, which includes the maintenance and protection of heritage buildings. One of the essential parts of the preservation process is the reuse of the building, whereby an actual or new function is given to the building to preserve, sustain and reconfigure it in a way that preserves its originality, composition, and balance without compromising its relationship with the environment. The research problem is the fragile focus on the importance of functional value when starting the architectural preservation work, even though it requires an in-depth study of the extent of the impact of this change on preserving the heritage value of the building. The study aims to clarify the process of preservation in heritage buildings and the use of the rehabilitation process based on the architectural characteristics of the building. For this purpose, the analytical method approach of pre-and post-conservation blueprints was used through photographs to illustrate the impact of functional change in preserving the building’s heritage value. From here, the research concludes that preserving the permanence of the architectural heritage can be achieved through cooperation between all values and that the functional value significantly affects the permanence of the heritage building